The Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2020 (J‐SSCG 2020). Issue 1 (26th August 2021) - Egi, Moritoki; Ogura, Hiroshi; Yatabe, Tomoaki; Atagi, Kazuaki; Inoue, Shigeaki; Iba, Toshiaki; Kakihana, Yasuyuki; Kawasaki, Tatsuya; Kushimoto, Shigeki; Kuroda, Yasuhiro; Kotani, Joji; Shime, Nobuaki; et al.
Abstract : The Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2020 (J‐SSCG 2020), a Japanese‐specific set of clinical practice guidelines for sepsis and septic shock created as revised from J‐SSCG 2016 jointly by the Japanese Society of Intensive Care Medicine and the Japanese Association for Acute Medicine, was first released in September 2020 and published in February 2021. An English‐language version of these guidelines was created based on the contents of the original Japanese‐language version. The purpose of this guideline is to assist medical staff in making appropriate decisions to improve the prognosis of patients undergoing treatment for sepsis and septic shock. We aimed to provide high‐quality guidelines that are easy to use and understand for specialists, general clinicians, and multidisciplinary medical professionals. J‐SSCG 2016 took up new subjects that were not present in SSCG 2016 (e.g., ICU‐acquired weakness [ICU‐AW], post‐intensive care syndrome [PICS], and body temperature management). The J‐SSCG 2020 covered a total of 22 areas with four additional new areas (patient‐ and family‐centered care, sepsis treatment system, neuro‐intensive treatment, and stress ulcers). A total of 118 important clinical issues (clinical questions, CQs) were extracted regardless of the presence or absence of evidence. These CQs also include those that have been given particular focus within Japan. This is a large‐scale guideline covering multiple fields; thus, in addition to the 25 committee members, we had the participation and support of a total of 226 members who are professionals (physicians, nurses, physiotherapists, clinical engineers, and pharmacists) and medical workers with a history of sepsis or critical illness. The GRADE method was adopted for making recommendations, and the modified Delphi method was used to determine recommendations by voting from all committee members. As a result, 79 GRADE‐based recommendations, 5 Good Practice Statements (GPS), 18 expert consensuses, 27 answers to background questions (BQs), and summaries of definitions and diagnosis of sepsis were created as responses to 118 CQs. We also incorporated visual information for each CQ according to the time course of treatment, and we will also distribute this as an app. The J‐SSCG 2020 is expected to be widely used as a useful bedside guideline in the field of sepsis treatment both in Japan and overseas involving multiple disciplines.